The Effect of Fuel Prices and Weather Changes on Fishermen’s Income in Coastal Villages of Leitimur Selatan, Maluku - Anna Valensia Christianty (Jurnal Mirai Management, 2026)
The capture fisheries sector in Hukurila, Kilang, and Rutong Villages, South Leitimur District, faces a dual challenge characterized by rising operational costs stemming from fuel price fluctuations and ecological disruptions induced by extreme weather events. This study aims to analyze the partial and simultaneous impact of these variables on fishermen’s income. Employing a quantitative approach utilizing multiple linear regression analysis on 78 respondents, this study examines the economic sensitivity of fishermen to external shocks. The analytical results demonstrate that fuel prices and weather changes simultaneously exert a significant influence on fishermen’s income, yielding an R-Square value of 0.882. This finding indicates that 88.2% of the variance in fishermen’s income is determined by these two variables. These findings confirm that fishermen are experiencing systemic economic pressure, rendering policies centered solely on operational subsidies ineffective in the absence of climate risk mitigation. The study concludes by emphasizing the necessity of holistic and adaptive coastal economic resilience strategies to enhance fishermen's welfare. These results are expected to serve as a strategic reference for local governments in designing targeted, evidence-based policy interventions